Information overload, psychological ill-being, and behavioral intention to continue online healthcare information search. (May 2017) - Swar, Bobby; Hameed, Tahir; Reychav, Iris
Abstract: Internet these days have been extensively used to access and search health information supplementing or substituting the traditional sources of online health information (OHI) like health professionals. With the increase in online health information search the production of health information on internet is also rapidly increasing. Due to the enormous volume of health information available on internet, it is hard to locate, process and manage the required valuable information effectively often overloading health information seekers. Information overload phenomenon occurs when more information is presented than the ability of information seekers to process and handle the information. Researchers argue that information overload phenomenon is significantly associated with health-related issues of information seekers. Therefore, the aim of this study is to empirically examine how OHI related information overload impacts the psychological state of information seekers and their behavioral intention to continue the use of OHI search. A research model based on Information Processing Theory and Theory of Planned Behavior is developed and tested using the data collected from 380 survey responses. The results show that perceived information overload has a positive impact on information seekers' psychological ill-being influencing their behavioral intention to discontinue the use of OHI search. Theoretical and practical implications are discussed at the end of the paper. Highlights: Information overload positively related with seekers' psychological ill-being. Higher psychological ill-being negatively impact the intention to continue search. Filtering rules, user awareness, and shared content may reduce information overload.